Resposta imune inespecífica e específica humoral de bezerros curraleiro e nelore vacinados com mycobacterium bovis - BCG - Lobo, Joyce Rodrigues (2009)
Curraleiro breed was formed in regime of extensive breeding on region of cerrado, with minimal attention to infectious diseases and alimentary, resulted in animals extremely rustic that composed an important genetic recourse for Brazilian livestock. In order to improve the understanding about immunological aspects this breed, a comparative study between Curraleiro and Nelore calves after immunization with BCG vaccine. Was realized the quantity of IgM and IgG antibodies specifics to Mycobacterium bovis, by indirect ELISA in house method. Was determined twelve young calves (six month of age) were used throughout the study. The animals were divided in two groups: six calves from Curraleiro breed and six calves from Nelore breed. Each group was further divided in: immunized group which received the BCG vaccine and a control which received the adjuvant. The data were submitted to descriptive statistics and then to the Kruskall Wallis and Mann-Whitney tests. It was realized hemogram, total protein, albumin, globulin eletroforesis of serological protein, ELISA for M. bovis IgG and IgM levels. The results were grouped and Curraleiro and Nelore calves were compared, the Curraleiro breed exhibited larger numbers of leucocytes, neutrophils, lymphocytes and monocytes; higher proteins and globulins levels; and higher concentration of alfa-1, beta and gama globins fraction. So, considered the vaccination to BCG, the Curraleiro calves were more levels in produce specifics M. bovis IgM and IgG. Between the immunized groups, Curraleiro group immunized presented better performance than Curraleiro control group, Nelore group immunized and lastly Nelore control group. Concluded that Curraleiro breed compared to Nelore breed exhibited unspecific and specific humoral immune response more productive qualified for bigger numbers of leucocytes and higher concentration of unspecific and specific immunoglobulin.